ANALISIS KESANTUNAN BERBAHASA ANTARA DOSEN DAN MAHASISWA BAHASA INDONESIA UNIVERSITAS MUHAMMADIYAH BONE (KAJIAN PRAGMATIK) - Rastina; Muh. Safar; Muhammad Idris (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the forms of politeness used in interactions between lecturers and students in the Indonesian Language Education Study Program at the University of Muhammadiyah Bone. This study uses a descriptive qualitative approach with the main theory of the principle of politeness from leech. The research data are in the form of lecturers' and students' utterances that occur in the learning process of poetry appreciation courses. Data collection techniques include observation, conversation recaps. The results of the study indicate that the forms of politeness in the interactions of lecturers and students include the maxim of wisdom, the maxim of generosity, the maxim of humility, the maxim of praise, the maxim of agreement, and the maxim of sympathy. This study is expected to be a reference in understanding the importance of language ethics in academic environments, as well as contributing to pragmatic studies in the field of education.